The Rearrangement of the Archaeological Museum of Arcevia: Aiming to Improve Accessibility - Mauro Fiorentini (EXARC Journal, 2023)
The Marche region in central Italy hosts quite a number of archaeological museums, containing a wide range of specimens and collections that cover a time span from the Palaeolithic onwards. From Stone Age votive statues to Iron Age weaponry, from Greek and Celtic luxurious jewellery and pottery to unmatched Roman finds; local museums preserve a huge variety of specimens that are of great interest to the public, scholars and amateurs alike.